William Edward Riley papers - Riley, William Edward, 1897-
Correspondence, memoranda, operation plans and reports, notes, maps, photographs, and other papers relating to Riley's World War II service on the staff of Admiral William Frederick Halsey, commander of South Pacific Area and commander in chief of the U.S. Navy 3rd Fleet.; invasions of the Philippines and Ulithi (Micronesia); and U.S. Marine Corps and U.S. Navy demobilization efforts after the war. Includes speeches by James Forrestal, William Frederick Halsey, Thomas C. Kinkaid, William D. Leahy, and Kenneth C. Royall.
U.S. Marine Corps officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Forrestal, James, -- 1892-1949.; Halsey, William Frederick, -- 1882-1959.; Kinkaid, Thomas C. -- 1888-1972.; Leahy, William D; Royall, Kenneth C. -- 1894-1971.; United States. -- Marine Corps -- Demobilization; United States. -- Marine Corps -- Officers; United States. -- Navy -- Demobilization; United States. -- Navy. -- Fleet, 3rd.; World War, 1939-1945 -- Campaigns -- Micronesia; World War, 1939-1945 -- Campaigns -- South Pacific Ocean; World War, 1939-1945 -- Campaigns -- Philippines; World War, 1939-1945 -- Naval operations, American; Ulithi (Micronesia); Marine Corps officers